Is There Private Information in the FX Market? The Tokyo Experiment - Ito, Takatoshi; Lyons, Richard K.; Melvin, Michael T. (Journal of Finance, 1998)
We provide evidence of private information in the foreign exchange market. The evidence comes from the introduction of trading in Tokyo over the lunch hour. Lunch-return variance doubles with the introduction of trading, which cannot be due to public information since the flow of public information did not change with the trading rules. We then exploit microstructure theory to discriminate between the two alternatives: private information and mispricing. Four key results support the predictions of private-information models. Three of these involve changes in the intraday volatility U-shape. The fourth is that opening trade causes mispricing's share in variance to fall.